Costing electronic private sector malaria surveillance in the Greater Mekong Subregion - Ann Levin; Rebecca Potter; Kemi Tesfazghi; Saysana Phanalangsy; Phally Keo; Elijah Filip; Si Hein Phone; M. James Eliades (Malaria Journal, 2021)
Abstract Background Private sector malaria programmes contribute to government-led malaria elimination strategies in Cambodia, Lao PDR, and Myanmar by increasing access to quality malaria services and surveillance data. However, reporting from private sector providers remains suboptimal in many settings. To support surveillance strengthening for elimination, a key programme strategy is to introduce electronic surveillance tools and systems to integrate private sector data with national systems, and enhance the use of data for decision-making. During 2013–2017, an electronic surveillance system based on open source software, District Health Information System 2 (DHIS2), was implemented as part of a private sector malaria case management and surveillance programme. The electronic surveillance system covered 16,000 private providers in Myanmar (electronic reporting conducted by 200 field officers with tablets), 710 in Cambodia (585 providers reporting through mobile app), and 432 in Laos (250 providers reporting through mobile app). Methods The purpose of the study was to document the costs of introducing electronic surveillance systems and mobile reporting solutions in Cambodia, Lao PDR, and Myanmar, comparing the cost in different operational settings, the cost of introduction and maintenance over time, and assessing the affordability and financial sustainability of electronic surveillance. The data collection methods included extracting data from PSI’s financial and operational records, collecting data on prices and quantities of resources used, and interviewing key informants in each setting. The costing study used an ingredients-based approach and estimated both financial and economic costs. Results Annual economic costs of electronic surveillance systems were $152,805 in Laos, $263,224 in Cambodia, and $1,310,912 in Myanmar. The annual economic cost per private provider surveilled was $82 in Myanmar, $371 in Cambodia, and $354 in Laos. Cost drivers varied depending on operational settings and number of private sector outlets covered in each country; whether purchased or personal mobile devices were used; and whether electronic (mobile) reporting was introduced at provider level or among field officers who support multiple providers for case reporting. Conclusion The study found that electronic surveillance comprises about 0.5–1.5% of national malaria strategic plan cost and 7–21% of surveillance budgets and deemed to be affordable and financially sustainable.